Desenvolvimento profissional docente na interlocução universidade e escola de educação básica - Leirias, Cláudia Martins (2017)
The present study has as its theme the professional teacher development in educational contexts involving the partnership of the University, through the graduate program, and the public Basic Education School. The thesis is focused on the defense of professional development projects built in interaction processes between the University and the School of Basic Education when guided by principles that recognize education as human possibility (VIEIRA PINTO, 1982) contribute to the experience of the teachers as intellectuals transformers. The study anchored in the contributions of Álvaro Vieira Pinto, Anísio Teixeira, Darcy Ribeiro, Paulo Freire, E. P. Thompson, W. Benjamin, H. Giroux, Carlos Marcelo, Korthagen, C. Day, K. Zeichner, Antonio Nóvoa, Siti Fernandes and Marli André. It was on the intentionality of methodical reflection and production of scientific knowledge as a manifestation of the historicity and rationality and the transformation of educational reality of the country. The research has as main issue how the pedagogical supervisory understands the dialogue of the University and School of Basic Education in its professional development. It intends to contribute to the production of knowledge in the field of training teachers, in the context of implementation of educational policies that involve the University partnership with the Basic Education School and involving research related to training programs. It is a study with a qualitative approach proposed to find the objective of the research. It was based on the principles of the case study, with the production of narratives involving the participation of pedagogical supervisory that integrated the OBEDUC Project/PUCRS in 2011 to 2014 period, analysis of the context of the production of texts (s. Ball) guiding educational policy and realization of unsystematic observation. For the analysis of the collected data have been used the principles of content analysis, with elaborate frames-synthesis and realization of data triangulation. Research results make it possible to reaffirm the need for professional development processes built in partnership between the University and the School of Education. It involves the recognition of the complexity of the phenomenon, as well as, the recognition of the emancipatory possibilities of formative processes which theoretical perspective-research methodology with participatory approaches as pedagogic-political and epistemological southern guiding principle and understanding of the specificities of the field of training teacher.